K.H. HASYIM ASY'ARI'S UNDERSTANDING OF TAHLILAN-YASINAN (A CRITICAL ANALYSIS STUDY OF HADITH PERSPECTIVES) - Khofifah Amanah; Hendri Waluyo Lensa (CV. Adiba Aisha Amira, 2024)
This research presents a comprehensive analysis of K.H. Hasyim Asy'ari's thoughts on tahlilan-yasinan which refers to the hadith perspective on intergroup differences of opinion in Indonesia. The researcher uses a historical qualitative research method that relies on searching and analyzing literature studies and document studies that lead to biographical research, as well as several internet sources and K.H. Hasyim Asy'ari's direct works. The results showed that K.H. Hasyim Asy'ari's da'wah became a boomerang point for Islam today, that he was less comprehensive by looking at and preaching only from one side and not studying and paying attention to the actual aspects of the Indonesian nation. He aims to allow tahlil and continue the relay of Walisongo's da'wah but forgets the important side of the da'wah and practice, the detailed procedures and practices, so that many religiously based bid'ah activities appear in the midst of Indonesian society. Islam does not prohibit sharing food with the brotherhood, Islam also does not prohibit dhikr and reading the Qur'an, but if specialize in practices that are not in accordance with the guidance of the Prophet ﷺ, this will be a bid'ah that will harm our rself tomorrow.